Absolute blood contrast concentration and blood signal saturation on myocardial perfusion MRI: Estimation from CT data - Ishida, Masaki; Sakuma, Hajime; Murashima, Shuichi; Nishida, Junko; Senga, Masayo; Kobayasi, Shigeki; Takeda, Kan; Kato, Noriyuki (Journal of magnetic resonance imaging, 2009)
Purpose To determine the optimal contrast injection rate and absolute blood gadolinium concentration for optimal first‐pass imaging. Materials and Methods The concentration of contrast medium in left ventricle (LV) was estimated from dynamic computed tomography (CT) by administering iodinated contrast medium of volume (0.2 mL/kg) equivalent to 0.1 mmol/kg of gadolinium injection in 50 subjects. A blood sample study was performed to determine the relationship between blood signal and gadolinium concentration on perfusion MRI. Results The mean peak gadolinium concentration in LV increased as the injection rate increased from 1 mL/sec (3.7 ± 1.2 mM), to 4 mL/sec (6.9 ± 2.7 mM) (P < 0.01). However, no significant improvement was found with an increase in the injection rate from 4 mL/sec to 5 mL/sec (6.8 ± 1.5 mM, P = 0.86). In a blood sample study the linear relationship between blood signal and gadolinium concentration was maintained in the range of ≤0.67 mM (r = 0.992), which corresponds to a peak blood concentration following a 0.01 mmol/kg gadolinium injection. Conclusion The optimal contrast injection rate for myocardial perfusion magnetic resonance imaging (MRI) appears to be 4 mL/sec. Saturation of arterial input signal is inevitable if the dose of gadolinium contrast medium exceeds 0.01 mmol/kg. These findings are essential for accurate quantification of myocardial blood flow from perfusion MRI. J. Magn. Reson. Imaging 2009;29:205–210. © 2008 Wiley‐Liss, Inc.